Framework of Malaysian Private Retirement Scheme under Capital Markets and Services Act 2007 - Yeon, Asmah Laili; Hussain, Mohammad Azam; Ramli, Azlin Namili (International Journal of Economics and Financial Issues, 2016)
The Government of Malaysia established the 1 Malaysia Pension Scheme (SP1M) in 2010 and recognizes the importance of savings from an early age to ensure sufficient savings after retirement. After five years been introduced to the public, it is significance to evaluate the perception of PRS providers in relation to the existing legal framework of the scheme. The objective of the paper is to examine the perception of PRS providers on the legal framework of the private retirement scheme. This is a qualitative research and interviews were conducted amongst providers of PRS. In analysing the data, thematic data analysis was employed to deduce findings from the respondents' views. The finding shows that majority of respondents agreed the legal framework of PRS is adequate to protect investors and providers. However, there are a few suggestions to improve the legal frameawork and governance of PRS i.e. internal guidelines, provider's fee and etc. Keywords: Retirement Scheme, Investors' Protection, Retirement Saving, Legal Framework JEL Classifications: K2, K22, K220